Pengaruh Penerapan Sistem Keuangan Desa (SISKEUDES), Pengendalian Internal dan Kompetensi SDM Terhadap Akuntabilitas Pengelolaan Dana Desa Melalui Sikap Qana’ah Sebagai Variabel Intervening di Kecamatan Bengkalis - Dariana, Dariana; Sari, Novita; Nirwana, Ema (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the effect of implementing the village financial system (Siskeudes), internal control, and human resource competence on the accountability of village fund management through the attitude of qana'ah as an intervening variable in Bengkalis District. It was carried out to analyze the influence on local government performance, including the influence of implementing the village financial system (Siskeudes), internal control, and human resource competency on fund management accountability through qana'ah attitude as an intervening variable in Bengkalis district. The type of research used in this research is quantitative research. The method used in this research is the descriptive method. The data obtained were then analyzed using SPSS 25. The test results show that the influence of implementing the village financial system (Siskeudes), internal control, and HR competence has a positive and significant effect on fund management accountability. Besides that, the implementation of the Village Financial System (Siskeudes), Internal Control, and HR Competence has no significant effect on Fund Management Accountability or the attitude of Qana'ah as an intervening variable.Keywords: SISKEUDES, Internal Control, HR Competence, Qana'ah Attitude, Accountability and Fund Management.